Flow cytometric assay of platelet glycoprotein receptor numbers in hypercholesterolemia - ÖZSAVCI, DERYA (TAYLOR & FRANCIS INC, 2002)
In this study, platelet glycoprotein (Gp) receptor numbers were measured by a flow cytometric assay using Cytoquant Gp in seven hypercholesterolemic and five normal subjects. Thrombin receptor agonist peptide (TRAP) was used to activate platelets. In hypercholesterolemia the Gp receptor numbers per resting platelet were found to be: 38 629 +/- 8538 (GpIIb/IIIa), 22 269 +/- 5628 (GpIb), 37 037 +/- 9810 (GpIIIa), 224 +/- 504 (CD62-P). After activation, receptor numbers were determined to be: 56 399 +/- 9003 (GpIIb/ IIIa), 10 970 +/- 5319 (GpIb), 50 715 +/- 7904 (GpIIIa), 1222 +/- 687 (P-selectin). In the normal group before the activation, receptor numbers were: 43 828 +/- 8862 (GpIIb/ IIIa), 22 166 +/- 3847 (GpIb), 42 351 +/- 1049 (GpIIIa), 62 +/- 139 (CD62-P), After activation, receptor numbers were determined to be: 60 573 +/- 4294 (GpIIb/ IIIa), 13 003 +/- 4118 (GpIb), 52 067 +/- 1039 (GpIIIa), 3608 +/- 1508 (CD62-P). In hypercholesterolemic subjects, GpIIb/ IIIa and GpIIIa receptor numbers on activated platelets increased significantly, whereas P-selectin numbers remained unchanged. However, the GpIb levels decreased significantly. In the control group, after activation, GpIIb/ IIIa and P-selectin receptors increased significantly, GpIIIa receptor numbers did not change significantly, whereas GpIb receptor numbers decreased significantly. When the GpIIb/ IIIa, GpIb, GpIIIa receptor numbers of the control group and hypercholesterolemic group were compared before and after activation, no significant changes were observed (P>0.05). But P-selectin receptor numbers were significantly decreased in hypercholesterolemic patients compared to normals following TRAP activation (P<0.05). In this study, the effect of hypercholesterolemia on platelet function was observed. The striking observation about present study was the marked decrease in P-selectin expression after activation in the hypercholesterolemics compared to normals. This finding suggests some sort of platelet dysfunction in these individuals.
Keywords: ACTIVATED PLATELETS; WHOLE-BLOOD; IIB-IIIA; SURFACE GLYCOPROTEINS; MONOCLONAL-ANTIBODY; IN-VITRO; FIBRINOGEN; THROMBIN; MECHANISMS; ANTIGENS